1998
DOI: 10.1016/s0886-3350(98)80270-8
|View full text |Cite
|
Sign up to set email alerts
|

Determining the imaging quality of intraocular lenses

Abstract: Either criterion may be applied in accordance with a proposed international standard for IOLs. The model eye method can be applied over a broader range of dioptric powers and is relevant for materials that interact with aqueous. Both tests appear to have a greater ability to detect unwanted surface aberrations than resolution testing of IOLs in a water cell using parallel light, a method described in the current American National Standards Institute standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 14 publications
1
35
1
Order By: Relevance
“…Experimental studies using several methods, including modulation transfer function, clarified that the optical quality of the IOL differs by optic design, optic material, and dioptres. [29][30][31][32] Our clinical study also suggests that spherical aberration of the internal optics varies according to optic design, optic material, and possibly dioptric power of the implanted IOL. Furthermore, there Figure 2 Comparisons of the mean (7SD) ocular (a), corneal (b), and internal optic (c) aberrations between eyes that received the five different types of IOL.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Experimental studies using several methods, including modulation transfer function, clarified that the optical quality of the IOL differs by optic design, optic material, and dioptres. [29][30][31][32] Our clinical study also suggests that spherical aberration of the internal optics varies according to optic design, optic material, and possibly dioptric power of the implanted IOL. Furthermore, there Figure 2 Comparisons of the mean (7SD) ocular (a), corneal (b), and internal optic (c) aberrations between eyes that received the five different types of IOL.…”
Section: Discussionmentioning
confidence: 56%
“…12,13,[29][30][31][32][33][34][35] It has been also shown that the higher-order aberration of pseudophakic eyes is comparable with that of phakic eyes of subjects of the same age, and is greater than that of young phakic eyes. [11][12][13] Recently, to compensate for the positive spherical aberration of the cornea, a prolate IOL with negative spherical aberration, the so-called aspherical IOL, has been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The optical quality of isolated IOLs has received considerable attention, and most IOLs have a better optical quality than crystalline lenses. However, IOLs with better optical quality does not show the same optimal quality in vivo as expected in optical laboratory system.…”
Section: Introductionmentioning
confidence: 99%
“…However, IOLs with better optical quality does not show the same optimal quality in vivo as expected in optical laboratory system. [1][2][3] One explanation is that optical quality is governed by both the cornea and the IOL. Studies have shown that cornea aberrations are at least partially compensated by lenticular aberrations in young human eyes.…”
Section: Introductionmentioning
confidence: 99%